2011
DOI: 10.4314/ejhs.v21i2.69055
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Uropathogens in Urinary Tract Infection and Antibiotic Susceptibility Pattern in Jimma University Specialized Hospital, Southwest Ethiopia

Abstract: BackgroundUrinary tract infection (UTI) is one of the most common bacterial infections encountered by clinicians in developing countries. Area-specific monitoring studies aimed to gain knowledge about the type of pathogens responsible for urinary tract infections and their resistance patterns may help the clinician to choose the correct empirical treatment. Therefore, the aim of this study was to determine the type and antibiotic resistance pattern of the urinary pathogens isolated from patients attending Jimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

59
139
9
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(234 citation statements)
references
References 19 publications
(25 reference statements)
59
139
9
4
Order By: Relevance
“…aspirin/naproxen with duloxetine) If not possible, then the dosing interval was changed (e.g. amitriptyline with duloxetine and linezolid combination)( Table 7, 8,9). The outcome of the most (68; 64.1%) of the patients showed were improved, followed by stable (26; 24.5%), died (5; 4.7%) and worsened control and monitoring of the chronic disease condition help in avoiding recurrence of UTIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aspirin/naproxen with duloxetine) If not possible, then the dosing interval was changed (e.g. amitriptyline with duloxetine and linezolid combination)( Table 7, 8,9). The outcome of the most (68; 64.1%) of the patients showed were improved, followed by stable (26; 24.5%), died (5; 4.7%) and worsened control and monitoring of the chronic disease condition help in avoiding recurrence of UTIs.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies showed that increased mortality associated with bacterial infections, in older UTI patients was more and extensive need for prevention with early diagnosis of UTI is vital to reduce morbidity and mortality. 9 Antibiotics play a vital role in the treating of bacterial UTIs and in the majority of cases the initial empirical treatment is with broad spectrum antibiotics. 10 Unfortunately, this trend of antibiotic usage leads to antibiotic resistance, the emergence of multi-drug resistant (MDR) strains (Clostridium difficile infection) and adverse drug reactions (ADRs).…”
Section: Introductionmentioning
confidence: 99%
“…Urine samples were cultured on 5% blood agar, MacConkey, and Eosin-Methylene blue (EMB) agar (Oxoid Ltd, Bashingstore, Hampire, UK) using calibrated loops for semi-quantitative method (16) and incubated in both aerobic and anaerobic conditions for 24 hours at 37°C. Cultures without any colony at the end of 24h incubation were further incubated for 48h.…”
mentioning
confidence: 99%
“…In recent years, resistance to antibiotics is a great public health problems posed in the world, Resistance to antibiotics as a threat to human health, which is on the rise. Multi drugresistant E. coli infections increased annual and it is a serious problem [14,15]. that they are easy to synthesize by different of bacteria [16].…”
Section: Introductionmentioning
confidence: 99%